Tinjauan Kinerja Keuangan dan Kebijakan Dividen terhadap Nilai Perusahaan - Yudha Aditya; M. Hendri Yan Nyale (J-MAS (Jurnal Manajemen dan Sains), 2022)
The consumer goods industry is one of the sectors that can increase the country's economic growth and can survive in any conditions so that it has the best performance opportunity than other sectors. the goods industry is able to contribute to the country by 58% even the consumption sector index has only decreased by 5.5% since the last 10 years. This study was conducted to determine the effect of financial performance in the form of profitability, leverage, liquidity and dividend policy on firm value, the theory used is signal theory. The population uses the consumer goods industrial sector for the period 2017-2021 as many as 76 companies and a sample that can be opened is 14 companies using purposive sampling technique. Analysis in this study using SPSS software, data analysis used descriptive statistics, classical assumption tests include normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. For the hypothesis use, t test, and the coefficient of determination (R2) using multiple linear regression analysis. The results of this study indicate that profitability and dividend policy have a significant positive effect on firm value, while leverage and liquidity have no significant effect on firm value.